Prenatal diagnosis and clinical management of cardiac rhabdomyoma: a single-center study - Peng, Longzhuang; Cai, Youchun; Wu, Jianhang; Ling, Wen; Wu, Qiumei; Guo, Shan; Huang, Biying; Jiang, Caihong; Weng, Zongjie (Frontiers in Cardiovascular Medicine, 2024)
Objective The study aims to assess the ultrasonic features of fetal cardiac rhabdomyoma (CR), track the perinatal outcome and postnatal disease progression, investigate the clinical utility of ultrasound, MRI and tuberous sclerosis complex (TSC) gene analysis in CR evaluation, and offer evidence for determing of fetal CR prognosis. Methods We conducted a retrospective analysis of prenatal ultrasound-diagnosed fetal CR cases in our hospital from June 2011 to June 2022, tracked the perinatal outcomes, regularly followed live infants to analyze cardiac lesion changes and disease progression, and compared the sensitivities of ultrasound, MRI and their combination in the detecting of intracranial sclerosing nodules. Results Our study included 54 fetuses with CR: 32 pregnancies were terminated, 22 were delivered, 35 were diagnosed with TSC, 13 had simple CR without TSC, and in 6 cases, remained unclear whether TSC accompanied the CR due to insufficient evidence. 45 fetuses (83.3%) had multiple lesions, while 9 fetuses (16.7%) presented with a single lesion. Twelve cases had intracardiac complications, all associated with multiple lesions, and these cases exhibited larger maximum tumor diameters than the non-complicated group. Multiple intracardiac lesions were more prevalent in the TSC group than in the simple CR group. However, there was no significant difference in maximum tumor diameter between the two groups. Among 30 fetuses who underwent fetal brain MRI, 23 were eventually diagnosed with TSC, with 11 fetuses showing intracranial sclerosis nodules by ultrasound and 15 by MRI, and the diagnostic consistency was moderate (k = 0.60). Twenty-two fetuses were born and followed up for 6–36 months. CR lesions diminished or disappeared in 18 infants (81.8%), while they remained unchanged in 4 infants (18.2%). Ten out of 12 (83.3%) surviving children diagnosed with TSC developed epilepsy, and 7 (58.3%) had neurodevelopmental dysfunction. Conclusions The majority of CR cases involve multiple lesions, which are a primary risk factor for TSC. Through prenatal ultrasound examination is crucial for assessing fetal CR prognosis. Although ultrasound combined with MRI can detect intracranial sclerosis nodules in TSC fetuses, its sensitivity is limited. TSC gene sequencing is an essential diagnostic method. Simple CR cases without TSC generally have a favorable prognosis.